Characteristics of secondhand cannabis smoke from common smoking methods: Calibration factor, emission rate, and particle removal rate. (1st December 2020) - Zhao, Tongke; Cheng, Kai-Chung; Ott, Wayne R.; Wallace, Lance; Hildemann, Lynn M.
Abstract: The widespread legalization of recreational cannabis use raises growing concerns about exposure to secondhand cannabis smoke (SCS). However, few studies are characterizing fine particulate matter (PM2.5 ) exposure from SCS. Here, we determined PM2.5 calibration factors (CFs) for SCS from four common cannabis consuming methods—glass pipe smoking, joint smoking, bong smoking, and cannabis pen vaping—for widely used optical monitors (SidePak™ AM510, TSI Inc., Shoreview, MN) by comparing the monitors with gravimetric mass measurements. We furthermore investigated the emission rate, particle size distribution, and particle removal rate of SCS. The CFs of SidePak PM2.5 monitors measuring the four types of SCS were 0.31 (SE = 0.02), 0.39 (SE = 0.02), 0.40 (SE = 0.01), and 0.44 (SE = 0.03), respectively. The arithmetic mean emission rates of the four SCS sources were ~2–6 times that of secondhand tobacco smoke (STS) on a per-puff basis. The fresh SCS (1-min after smoking) showed a bimodal size distribution—one mode located at ~380–420 nm and another at ~800–840 nm. Under low-ventilation conditions, the indoor removal rates of SCS from cannabis vaping were slightly higher (i.e., 0.61–0.77/h) than those for the other three sources (i.e., 0.35–0.53/h). Graphical abstract: Image 1 Highlights: Emission rates of secondhand cannabis smoke were 2–6 times of tobacco smoke. Fresh secondhand cannabis showed a bimodal size distribution. The indoor removal rates of secondhand cannabis vaping were slightly higher.